(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Different solvent and extraction method are used to extract phytochemicals from the seeds of Carica papaya. The GC/MS analysis of MeOH extract identified potential antibacterial compounds such as isothiocyanatomethyl benzene, 9-octadenoic acid, hexadecenoic acid and Beta-sitole. Different extraction method is by extraction, distillation, maceration, solvent extraction. Aqueous extracts prepared from heattreated seeds had no anthelmintic activity or benzyl isothiocyanate content although both appeared when these extracts were incubated with a myrosinase-containing fraction prepared from papaya seeds. A 10 h incubation of crude seed extracts at room temperature led to a decrease in anthelmintic activity and fractionated samples showed a lower benzyl isothiocyanate content relative to non-incubated controls. Benzyl thiocyanate, benzyl cyanide, and benzonitrile were not detected in any preparations and cyanogenic glucosides, which were present, could not account for the anthelmintic activity detected. Thus, our results are best explained if benzyl isothiocyanate is the predominant or sole anthelmintic agent in papaya seed extracts regardless of how seeds are extract regardless of how seeds are extracted.